2005
DOI: 10.1353/pla.2005.0056
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of Interactive Multimedia for Library-User Education

Abstract: A test of the effectiveness of interactive multimedia Web sites demonstrates that library users' topic knowledge was significantly greater after visiting the sites than before. Library users want more such sites about library services, their majors, and campus life generally. Librarians describe the roles they want to play on multimedia production teams after working on the LUMENS Project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Similarly Karen Markey 7 and her colleagues describe how interactive multimedia "shows," used as tutorials, were created and tested for their effectiveness in conveying content information. Based on pre-and post-tests results, Markey and her colleagues found that not only were interactive multimedia tutorials useful teaching tools, they also were positively rated by library users.…”
Section: Grant and Brettle 5 Found An Interactive Web-based Tutorial mentioning
confidence: 99%
“…Similarly Karen Markey 7 and her colleagues describe how interactive multimedia "shows," used as tutorials, were created and tested for their effectiveness in conveying content information. Based on pre-and post-tests results, Markey and her colleagues found that not only were interactive multimedia tutorials useful teaching tools, they also were positively rated by library users.…”
Section: Grant and Brettle 5 Found An Interactive Web-based Tutorial mentioning
confidence: 99%
“…Findings from a study by Kekkonen-Moneta and Moneta [16] indicated that IMM had a significant effect on both students' achievement and their problem solving skills. Similarly, Markey et al [17] found that the experimental group had significant improvement gain in self-learning ability apart from of other variables. Experimental treatment included use of the interactive multimedia module.…”
Section: Interactive Multimedia (Imm) Researchmentioning
confidence: 83%
“…The probable of IMM for education has been considered widely in the 90's and continued to be investigated. For example, Markey [13] found that multimedia to be an effective approach for providing pre-service teachers with pre-observational experiences. In a similar area, Apte and Roesler [14] studied the utility of understanding teaching (an IMM program) for pre-service teachers.…”
Section: Interactive Multimedia (Imm) Researchmentioning
confidence: 99%
“…These results were not affected by gender, class rank, or previous knowledge of library resources, and the authors of the study felt that this was an indicator of the widespread utility of the multimedia format. Students in this study expressed the desire for multimedia websites on other library topics, with many indicating that they would recommend these sites to a friend (Markey, 2005). Beile and Boote (2005) examined the efficacy of online versus face-to-face library instruction by comparing three groups of students taking the same course in different formats.…”
Section: Literature Reviewmentioning
confidence: 99%